Threat hunting in the cloud : defending AWS, Azure and other cloud platforms against cyberattacks /: defending AWS, Azure and other cloud platforms against cyberattacks. (2021) - Kudrati, Abbas; Peiris, Chris; Pillai, Binil
No abstract available